The Mediating Factor of Work Discipline: Emotional Intelligence and Employee Performance - Irmawati, Irmawati; Suyono, Joko; Noviarani, Khurin In; Ratnasahara Elisabeth, Damarsari (INNOVATION RESEARCH JOURNAL, 2025)
This study aims to analyse the influence of emotional intelligence and spiritual intelligence on employee performance with work discipline as an intervening variable at the Sekretariat Daerah Kabupaten Gresik. This study was conducted using a quantitative descriptive approach. The population used in this study was 129 employees. The data in this study were obtained using a questionnaire collection technique. Data analysis was carried out using statistical methods with structural equation modelling (SEM) and partial least squares (PLS) modelling. The results of the study showed that emotional intelligence did not have a significant effect on performance but had an effect on work discipline and performance with work discipline as an intervening variable. Spiritual intelligence had a significant effect on performance, work discipline, and employee performance, with discipline as an intervening variable. And work discipline has an effect on employee performance. The suggestion given by the author is that the Sekretariat Daerah Kabupaten Gresik can improve emotional intelligence through training, strengthening spiritual intelligence in HR development programs, and continuous evaluation and monitoring.